PENGARUH MEDIA SOSAL TERHADAP LOYALITAS PELANGGAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI KOTA SINTANG - Paulus Paulus (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2025)
This study aims to analyze the impact of social media-based marketing strategies on customer loyalty among Micro, Small, and Medium Enterprises (MSMEs) in Sintang City. In the digital era, social media has become a strategic marketing tool for MSMEs to reach consumers more broadly and efficiently. This research employs a quantitative approach using a survey method involving 150 MSME owners as respondents. Data were collected through questionnaires and analyzed using Simple linear regression techniques. The findings reveal that active use of social media platforms such as Facebook, Instagram, and WhatsApp significantly influences customer loyalty. Factors such as customer interaction, engaging content, and digital promotions are proven to enhance customer trust and commitment toward the products or services offered. Furthermore, the study highlights that consistent communication through social media plays a pivotal role in building long-term relationships with customers. The implications of this study underscore the importance of training and mentoring programs for MSME actors to optimize the use of social media as a marketing tool. With the right strategies, MSMEs in Sintang city can enhance their competitiveness and maintain customer loyalty amidst increasingly intense market competition